A Review of the Efficacy and Safety for Biologic Agents Targeting IL-23 in Treating Psoriasis With the Focus on Tildrakizumab - Ghazawi, Feras M.; Mahmood, Farhan; Kircik, Leon; Poulin, Yves; Bourcier, Marc; Vender, Ronald; Wiseman, Marni C.; Lynde, Charles; Litvinov, Ivan V. (Frontiers in Medicine, 2021)
Psoriasis is a chronic and debilitating inflammatory immune-mediated skin disorder. Several cytokines including interleukin (IL)-23 were demonstrated to play a central role in the pathogenesis of this disease. Treatment options for psoriasis range from topical to systemic modalities, depending on the extent, anatomical locations involved and functional impairment level. Targeting cytokines or their cognate receptors that are involved in disease pathogenesis such as IL-12/23 (i.e., targeting the IL-12p40 subunit shared by these cytokines), IL-17A, IL-17F, IL-17RA, and TNF-α using biologic agents emerged in recent years as a highly effective therapeutic option for patients with moderate-to-severe disease. This review provides an overview of the important role of IL-23 signaling in the pathogenesis of psoriasis. We describe in detail the available IL-23 inhibitors for chronic plaque psoriasis. The efficacy, pharmacokinetic properties, and the safety profile of one of the most recent IL-23 biologic agents (tildrakizumab) are evaluated and reviewed in depth.